2013
DOI: 10.1155/2013/857019
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Coronary Arteries in Khat Chewers Presenting with Myocardial Infarction

Abstract: Background. Khat chewing is a common habit in Yemen despite increased evidence of its negative impact on the cardiovascular system. Aims. We aimed to study the epicardial coronary arteries in khat chewers presenting with myocardial infarction (AMI). Materials and Methods. A descriptive, cross-sectional study was conducted between November 2008 and May 2009 in Yemen. AMI patients who underwent coronary angiogram were enrolled and divided into groups (gp): gp1 (diabetic and khat chewers), gp2 (khat chewers and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…There were also similar findings from Yemen [ 28 ]. In addition to elevation of BP and HR, khat chewers were at higher risk of developing AMI and stroke [ 4 , 10 , 16 - 19 , 22 ]. We did not include some of the above studies in to the meta-analysis because they did not quantify the intended outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also similar findings from Yemen [ 28 ]. In addition to elevation of BP and HR, khat chewers were at higher risk of developing AMI and stroke [ 4 , 10 , 16 - 19 , 22 ]. We did not include some of the above studies in to the meta-analysis because they did not quantify the intended outcome.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its effects on BP, khat has also been associated with the increased incidence of acute coronary vasospasm and myocardial infarction (MI) [ 15 ]. As one of the constituents of khat, cathinone is reported to be associated with severe coronary vasoconstriction and a severe negative inotropic effect on the cardiac muscle, suggesting that coronary spasm contributes to the development of acute MI [ 10 , 16 ]. Furthermore, Al-Shami and Al-Motarreb, evaluated the effect of khat chewing on the coronary arteries in patients with history of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 347 AMI patients, Al-Motarreb et al, 32 confirmed coronary spasm as the main mechanism of AMI in khat users. Of the total AMI cases, 79% were Yemenis.…”
Section: Coronary Vessels Myocardium and Heart Failurementioning
confidence: 94%
“…The typical clinical presentation is one of an acute coronary syndrome with sudden‐onset chest pain, which can be the result of progression of atheromatous narrowing, vasospasm, plaque instability with thrombus formation, increased myocardial oxygen demand and direct myocyte toxicity . It is likely that the majority of cases are the result of sympathomimetic‐induced vasospasm of coronary arteries , but acute myocardial infarction as a result of plaque rupture and thrombus formation is the cause of angina symptoms in a significant minority of cases, and this is more likely to be the case following cocaine consumption, given its prothrombotic action .…”
Section: Chronic Conditionsmentioning
confidence: 99%